ANALISIS NORMA SUBYEKTIF, SIKAP TERHADAP PERILAKU DAN PERSEPSI KENDALI PERILAKU TERHADAP NIAT KARYAWAN MELAKUKAN TINDAKAN WHISTLEBLOWING - Putu Nuniek Hutnaleontina; I Wayan Sudiana; Ni Putu Widya Astuti (UNHI Press, 2019)
The purpose of this study was to examine the factors that influence employee intention to conduct whistleblowing actions based on the Theory of Planned Behavior (TPB) proposed by Ajzen and Fishben (1988). The variables used in this study are subjective norms, attitudes toward behavior and perceptions of behavior control as independent variables and the intention to conduct whistleblowing as the dependent variable. This research was conducted at the Tabanan District Attorney. The number of samples taken was 65 employees, with saturated sampling method (census). Data collection was carried out through interviews and questionnaires. The analysis technique used is multiple linear regression. This analysis is used to calculate the magnitude of the influence of subjective norms, attitudes toward behavior and perceptions of behavioral control on the intention to conduct whistleblowing actions. The results of this study state that subjective norms have a significant effect on employee intention to conduct whistleblowing actions. In addition, attitudes towards behavior also have a significant effect on employees' intention to conduct whistleblowing actions. Perceptions of behavioral control also have a significant effect on employee intentions to carry out whistleblowing actions.